2006
DOI: 10.1016/j.vetmic.2006.03.006
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence and characterization of Campylobacter jejuni and C. coli in organic pigs and their outdoor environment

Abstract: The occurrence and species distribution of thermophilic Campylobacter was investigated in organic outdoor pigs. An increased exposure of outdoor pigs to C. jejuni from the environment may cause a shift from a normal dominance of C. coli to more C. jejuni, which may imply a concern of reduced food safety.Bacteriological methods for determination of Campylobacter excretion level were combined with colony-blot hybridization and real-time PCR for specific detection of C. jejuni in pigs. Campylobacter was isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 32 publications
4
54
2
Order By: Relevance
“…and presence of wild birds which may have contributed to C. jejuni contamination. Similar results were obtained from the work done by Jensen et al, (2006). They observed that 35 per cent of environmental samples (soil and water) were positive for Campylobacter spp.…”
Section: Antibiotic Resistance Profilingsupporting
confidence: 84%
“…and presence of wild birds which may have contributed to C. jejuni contamination. Similar results were obtained from the work done by Jensen et al, (2006). They observed that 35 per cent of environmental samples (soil and water) were positive for Campylobacter spp.…”
Section: Antibiotic Resistance Profilingsupporting
confidence: 84%
“…This is in concordance with the general finding of high Campylobacter spp. prevalence in pigs and that colonisation may occur within the first day of life (Young et al, 2000;Jensen et al, 2006). However, in the 7-week-old piglets fed chicory for 2 weeks, the Campylobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence and distribution of C. jejuni and C. coli was investigated by Jensen et al (2006) in extensive swine farms in Denmark. The study showed high prevalence of Campylobacter spp.…”
Section: Campylobacter In Swine Carcassesmentioning
confidence: 99%